OPTIMALISASI KEUNTUNGAN PENJUALAN BAKSO DAN MIE AYAM MENGGUNAKAN PROGAM LINEAR METODE GRAFIK - Benaya Zaqi Sumantri; Ilham Cahya Nugraha, Christian Tomi Adji, Paduloh (Jurnal Ekonomi dan Bisnis, 2025)
In this study, a descriptive qualitative approach was applied to analyze the condition of the warung managed by Mr. Sutino. The research process includes project exploration, information gathering through relevant questions, and analysis of the data that has been obtained. The findings showed an increase in optimal production for bakso and chicken noodle, with an additional profit of Rp 8,318,200 every week. This result emphasizes the need to increase production capacity for both food items. In the business realm, the Small and Medium Enterprises (SMEs) sector in Indonesia has a substantial influence. The application of integer programming as a linear programming method serves to optimize production by considering integer variables. In addition, the graphical method is used to reduce production costs by minimizing expenses for material management. This research methodology includes data collection through observation, analyzing the impact of stalls on food production and distribution, developing mathematical models, and evaluating the impact of the resulting models. This research is expected to provide valuable insights for the development of business strategies in the SME sector and become a reference for further research in similar fields.(Paduloh, Yunita, and Purba 2020)